A phase 2/3 randomized clinical trial followed by an open-label extension to evaluate the effectiveness of elamipretide in Barth syndrome, a genetic disorder of mitochondrial cardiolipin metabolism - Reid Thompson, W.; Hornby, Brittany; Manuel, Ryan; Bradley, Elena; Laux, Janice; Carr, Jim; Vernon, Hilary J. (Genetics in medicine, 2021)
Purpose To evaluate effectiveness of elamipretide in Barth syndrome (BTHS), a genetic condition of defects in TAZ , which causes abnormal cardiolipin on the inner mitochondrial membrane. Methods We performed a randomized, double-blind, placebo-controlled crossover trial followed by an open-label extension in BTHS to test the effect of elamipretide, a mitochondrial tetrapeptide that interacts with cardiolipin. In part 1, 12 subjects were randomized to 40 mg per day of elamipretide or placebo for 12 weeks, followed by a 4-week washout and then 12 weeks on the opposite arm. Ten subjects continued on the open-label extension (part 2) of 40 mg per day of elamipretide, with eight subjects reaching 36 weeks. Primary endpoints were improvement on the 6-minute walk test (6MWT) and improvement on a BTHS Symptom Assessment (BTHS-SA) scale. Results In part 1 neither primary endpoint was met. At 36 weeks in part 2, there were significant improvements in 6MWT (+95.9 m, p = 0.024) and BTHS-SA (-2.1 points, p = 0.031). There were also significant improvements in secondary endpoints including knee extensor strength, patient global impression of symptoms, and some cardiac parameters. Conclusion In this interventional clinical trial in BTHS, daily administration of elamipretide led to improvement in BTHS symptoms.